Summary judgement in construction contract - Sapeciay, Zukfli (2007)
The construction contract has built-in potential for conflicts and disputes to arise between the contracting parties. Disputes if not promptly resolved, will lead to losses and it is necessary for the parties to use the best method o f dispute resolution to resolve their disputes. Litigation is one o f the methods but the process takes substantial period to come to determination. Therefore, most disputes in construction contract are resolved by arbitration or mediation. In litigation process, there is a procedure that allows a litigatant to obtain quick judgm ent without going to trial. It is known as summary judgment procedure. However, it is available only in limited circumstances. Furthermore, it appears that it is not frequently used in construction contract cases. Therefore, this master project intends to identify the circumstances, limited as it may, that allow summary judgment to be available to the parties in a building contract. This research was carried out mainly through analysis o f cases reported in law journals, such as Malayan Law Journal, Building Law Report, etc. The result showed there were four circumstances where the summary judgment has been made available to the parties in a building contract in Malaysian construction cases. All these four circumstances were related to claims for progress payments that the employers (or the main contractors) refused or failed to pay to the main contractor (or the subcontractor as the case may be).In conclusion, it can be said that this summary judgment procedure is only suitable for actions claiming undisputed payment.